Reciprocity and Profit Sharing: Is There an Inverse U-shaped Relationship? - Cornelissen, Thomas; Heywood, John; Jirjahn, Uwe (Journal of Labor Research, 2014)
Free-riding potentially limits the effectiveness of profit sharing in motivating workers. While reciprocity can mitigate this problem, it need not be uniformly productive. We show that the probability of receiving profit sharing takes an inverse U-shape as detailed individual survey measures of reciprocity increase. This is consistent with moderate but not extreme reciprocity stimulating productivity. We support one potential causation path by showing that extreme positive (negative) reciprocity is associated with extremely high (low) socializing and among workers receiving profit sharing, an intermediate degree of socializing is associated with the maximum amount of paid and unpaid overtime, a productivity proxy.